Hip Arthroscopy and the Anterolateral Portal: Avoiding Labral Penetration and Femoral Articular Injuries - Aoki, Stephen Kenji (Elsevier, 2012)
Establishing the introductory viewing portal is a key step in hip arthroscopy. Most hip arthroscopists initially gain access to the central compartment of the hip through the anterolateral portal. Iatrogenic injury to the labrum or the femoral head chondral surface is a common yet under-reported complication of the procedure. Instead of directing the needle toward the clear space of the distracted joint, labral penetration can be minimized by directing the needle slightly anteroinferior to the clear space, overlapping the superior femoral head. Femoral head scuffing can be minimized by adjusting the position of the beveled needle and confirming a straight guidewire trajectory before trocar placement. This technical note addresses surgical pearls to minimize iatrogenic injury during initial central compartment access.